A light in dark times : the New School for Social Research and its university in exile - Friedlander, Judith, 1944- (Columbia University Press, 2019)
"Founded in 1919 in the name of academic freedom, the New School for Social Research quickly became a pioneer in adult education--what its first president, Alvin Johnson, called "the continuing education of the educated." During the 1920s, the New School became the place to go to hear famous people lecture on politics, the arts, and recent developments in new fields of inquiry such as anthropology and psychoanalysis. In 1933 Johnson opened the University in Exile within the New School, providing visas and jobs for nearly two hundred refugees fleeing Hitler. And through these exiled scholars, he re-created in miniature the great intellectual traditions of Europe's imperiled universities. In this book, Judith Friedlander reconstructs the history of the New School in the context of ongoing debates over academic freedom, intellectual dissidents, and democratic education. Against the backdrop of World War I and the first Red Scare, the Hitler years and McCarthyism, the student uprisings during the Vietnam War and the downfall of communism in Eastern Europe, Friedlander tells a dramatic story of academic, political, and financial struggle through brief sketches of New School administrators, faculty members, trustees, and students, among them Alvin Johnson and the political philosopher Hannah Arendt. As this unique educational institution prepares to celebrate its one hundredth anniversary, A Light in Dark Times offers a timely reflection on the New School's legacy, which can serve as an inspiration for the academic community today"--